Computational modelling of the aerodyanmics and flight mechanics of a boomerang - Prem, Parvathy. (2010)
The returning boomerang is a singularly interesting device: when thrown spinning in a near-vertical plane, rather than travelling along a straight line, the boomerang turns continuously to the left and ultimately returns to its thrower. The return of the boomerang is caused by two types of gyroscopic precession, the result of an interaction between the lift generated by the boomerang’s arms, and its initial angular velocity.